2010
DOI: 10.1590/s1516-14392010000300006
|View full text |Cite
|
Sign up to set email alerts
|

EValuation of the thixoformability of AA7004 and AA7075 alloys

Abstract: This study involved a complete evaluation of the thixoformability of AA7004 and AA7075 alloys, from their microstructural characterization to their viscous behavior. The alloys were subjected to globularization heat treatments for 0, 30, 90 and 210 seconds in two conditions of solid fractions, 45 and 60%, and to viscosity assays under the same conditions. Heat treatments promote the globularization of primary phase particles; hence, the best viscosity results were achieved for alloys with low solid fractions h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
(50 reference statements)
0
6
0
12
Order By: Relevance
“…5 vary in the range of 949 to 4678 μm 3 /s, which was much higher than the calculated one. Other investigators [14][15][16] observed higher coarsening rate in semi-solid processing experiment. Jain et al [14] in RSF process for 15% solid fraction obtained the experimental value of the coarsening rate constant about 322 µm 3 /s.…”
Section: Diffusive-lsw Theorymentioning
confidence: 84%
See 1 more Smart Citation
“…5 vary in the range of 949 to 4678 μm 3 /s, which was much higher than the calculated one. Other investigators [14][15][16] observed higher coarsening rate in semi-solid processing experiment. Jain et al [14] in RSF process for 15% solid fraction obtained the experimental value of the coarsening rate constant about 322 µm 3 /s.…”
Section: Diffusive-lsw Theorymentioning
confidence: 84%
“…Kaufmann et al [15] attained the coarsening rate of 166 and 430µm 3 /s for the new rheocasting and conventional thixocasting processes, respectively. Zoqui et al [16] investigated electromagnetic stirring rheocasting process and obtained coarsening rate constants about 1043 and 3099 µm 3 /s. Therefore, the competitive growth of particles related to diffusive Ostwald ripening could not be the only coarsening mechanism.…”
Section: Diffusive-lsw Theorymentioning
confidence: 99%
“…The methodology used here to assess the thixoformability of an alloy is the same as that described earlier by Zoqui et al (2008), Zoqui and Torres (2010) and Zoqui and Naldi (2011). The methodology adopted in the Foundry and Thixoforming Laboratory (FTL) at the Faculty of Mechanical Engineering, Unicamp, to evaluate the thixoformability of a specific alloy is based on six basic steps: (a) thermodynamic analysis of the solid-to-liquid transition; (b) manufacture of the alloy and characterization of its initial microstructure; (c) evaluation of microstructural stability in the semisolid state; (d) determination of the combined effect of the liquid fraction and the morphology of the remaining solid on the alloy's rheological behavior; (e) investigation of the thixoforming procedure itself; and (f) determination of the final microstructure and final mechanical characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Кроме того, совершенно оче-видно, что история подготовки и особенно чистота фидстоков играют определяющую роль для обеспечения малого разброса и высокого уровня свойств формируемого изделия. Анализ перспектив развития заготовительных производств из высокопрочных алюминиевых спла-вов, представленный в работах [7-9], привел в последующие годы к резкому росту объема исследований по тиксо-и реоштамповке де-формируемых сплавов [10][11][12][13][14][15], включая тиксоформинг сплавов си-стемы AlZnMgCu повышенной и особой чистоты.…”
Section: свойства тиксоштампованных деформируемых сплавовunclassified